Automated reasoning : 9th International Joint Conference, IJCAR 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 14-17, 2018, proceedings /: 9th International Joint Conference, IJCAR 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 14-17, 2018, proceedings. (2018) - Unknown
No abstract available